2021
DOI: 10.1152/japplphysiol.00424.2021
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cell and myonuclear accretion is related to training-induced skeletal muscle fiber hypertrophy in young males and females

Abstract: Satellite cells (SC) play an integral role in the recovery from skeletal muscle damage and supporting muscle hypertrophy. Acute resistance exercise typically elevates type I and type II SC content 24-96 hours post-exercise in healthy young males, although comparable research in females is lacking. We aimed to elucidate whether sex-based differences exist in fiber type-specific SC content after resistance exercise in the untrained (UT) and trained (T) states. Ten young males (23.0 ± 4.0y) and females (23.0 ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Fibers were excluded from analysis if they had a circularity <0.65. Fiber cross-sectional area was determined via the average of type I and type II fibers obtained from our previous publication (28).…”
Section: Methodsmentioning
confidence: 99%
“…Fibers were excluded from analysis if they had a circularity <0.65. Fiber cross-sectional area was determined via the average of type I and type II fibers obtained from our previous publication (28).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to inducing hypertrophy, numerous human studies have shown that the PRE-induced hypertrophic response is associated with myonuclear accretion [26,35]. Therefore, to determine whether WP induces this effect, we measured the myonuclei to fiber ratio in the mid-belly crosssections and found that WP increased this ratio.…”
Section: Wp Induces Hypertrophy and Myonuclear Accretion In The Plantaris Musclementioning
confidence: 96%
“…It has also been shown that the PRE-induced increase in muscle mass can be attributed to an increase in the cross-sectional area of muscle fibers (i.e., hypertrophy), and/or an increase in the length of muscle fascicles/fibers [23,24]. Moreover, these changes are often accompanied by an increase in the number of myonuclei per fiber, as well as a fast→slow transition in the composition of the Type II fibers [25,26]. Accordingly, we used a variety of different assays to determine whether these types of responses were elicited by our model which we refer to as "weight pulling".…”
Section: Introductionmentioning
confidence: 99%
“…Uncovering all the ways by which satellite cells affect non‐satellite cell populations during adult muscle adaptation, and translating these results to human populations, will be an exciting challenge for future investigations. More attention should also be paid to sex differences in satellite cell contributions to muscle adaptation, as this is incompletely understood 27,220,228,229 . Unfortunately, the vast majority of knowledge on satellite cell behavior during adaptation is extrapolated from developmental myogenesis or injury and regeneration experiments.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 99%
“… 212 , 213 , 214 , 215 , 216 , 217 Collectively, the amount and source of myonuclear turnover in adult skeletal muscle, and whether this is affected by exercise, are open questions that deserve further exploration. While muscle can adapt to an extent without satellite cells, it is currently unclear whether having augmented satellite cell number or function could enhance exercise adaptation through development and/or in adulthood; human resistance training studies point to this possibility in some instances, 35 , 182 , 218 , 219 , 220 , 221 but correlation does not mean causation. How satellite cells contribute to neuromuscular junction stability, as well as the myotendinous junction, are also provocative areas of inquiry, 50 , 222 , 223 , 224 , 225 especially in the context of exercise adaptation during aging.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 99%